Fully Implantable Neurostimulation System for Long-Term Behavioral Animal Study - Wonok Kang; Jinseung Lee; Wonsuk Choi; Jinseok Kim; Junesun Kim; Sung-Min Park (IEEE, 2023)
Spinal cord stimulation (SCS) is an emerging therapeutic option for patients with neuropathic pain due to spinal cord injury (SCI). Numerous studies on pain relief effects with SCS have been conducted and demonstrated promising results while the mechanisms of analgesic effect during SCS remain unclear. However, an experimental system that enables large-scale long-term animal studies is still an unmet need for those mechanistic studies. This study proposed a fully wireless neurostimulation system that can efficiently support a long-term animal study for neuropathic pain relief. The developed system consists of an implantable stimulator, an animal cage with an external charging coil, and a wireless communication interface. The proposed device has the feature of remotely controlling stimulation parameters via radio-frequency (RF) communication and wirelessly charging via magnetic induction in freely moving rats. Users can program stimulation parameters such as pulse width, intensity, and duration through an interface on a computer. The stimulator was packaged with biocompatible epoxy to ensure long-term durability under in vivo conditions. Animal experiments using SCI rats were conducted to demonstrate the functionality of the device, including long-term usability and therapeutic effects. The developed system can be tailored to individual user needs with commercially available components, thus providing a cost-effective solution for large-scale long-term animal studies on neuropathic pain relief.